(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Landscapes are paradigm cases for a theory of atmospheres like that of Hermann Schmitz since there are several atmospheres which can be experienced in landscapes. Though, landscape is rather seldomly picked out explicitly as a central theme in Schmitz’s work. An exception, however, is his article Landscape as a Mode of Perception, in which he argues that something becomes a landscape not by belonging to so-called nature, but by a specific mode of perception. I will critically analyze his conception of landscape and argue that landscape is more than a mode of perception: the aspect of naturalness must also be given. Corporeal communication with vastness and, that is, excorporation (Ausleibung), is not enough to understand what is specificity of the landscape. The inclusion of the dimension of naturalness allows us furthermore to better understand one of the most important functions of landscape, namely recovery, and the often-associated transcendence of the subject-object-dichotomy.